Методи контролю за викидами шкідливих відходів на атомних станціях - Єсипенко, В. Ю. (ХНУРЕ, 2023)
This text discusses the importance of controlling and minimizing harmful waste emissions in nuclear power plants. Several methods of handling radioactive waste, including storage, processing, and burial, are presented. Additionally, the use of emission-reducing technologies, such as advanced fuel technologies and chemical composition monitoring systems, are highlighted. The role of radiation control in limiting the release of harmful waste is also emphasized. Overall, the text serves as an introduction to the various methods used to manage and reduce the negative impact of nuclear power plant waste on the environment and human health.